Functional and metabolic dichotomy of murine γδ T cell subsets in cancer immunity - Lopes, Noëlla (2021)
© 2020 The Authors. European Journal of Immunology published by Wiley-VCH GmbH. This is an open access article under the terms of the Creative Commons Attribution License.